1978
DOI: 10.1055/s-0028-1098256
|View full text |Cite
|
Sign up to set email alerts
|

Santorini's Duct – An Insignificant Variant from Normal or an Important Overflow Valve?

Abstract: In a retrospective examination 250 consecutive pancreatograms obtained by ERCP were controlled on the existence of a D. Snatorini. Starting from the genetic development of the pancreatic ducts the question is investigated whether a second open pancreatic duct is responsible for a better drainage of the pancreas. Thus this duct may prevent hyperamylasemia and hyperlipasemia following ERCP. From an etiological point of view the elevation of these pancreatic enzymes is insufficiently understandable. If a D. Santo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

1979
1979
2004
2004

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…Berman et al (1960) suggested that the presence of a communicating accessory duct might reduce the incidence of pancreatitis by acting as a safety valve when the main duct was obstructed. This suggestion is supported to some extent by Mairose et al (1978) who found a three-fold increase in the incidence of hyperamylasaemia after ERCP in patients with an absent accessory pancreatic duct.…”
Section: Discussionmentioning
confidence: 72%
“…Berman et al (1960) suggested that the presence of a communicating accessory duct might reduce the incidence of pancreatitis by acting as a safety valve when the main duct was obstructed. This suggestion is supported to some extent by Mairose et al (1978) who found a three-fold increase in the incidence of hyperamylasaemia after ERCP in patients with an absent accessory pancreatic duct.…”
Section: Discussionmentioning
confidence: 72%
“…Accordingly, the reported patency of the APD of the typical pancreatic duct system (excluding cases of unfused pancreatic duct systems) has ranged widely, from 12% to 82% (Table 1). [2][3][4][5][6][7][8][9][10][11][12][13][14]37 Recently, some endoscopic retrograde pancreatography (ERP) studies have evaluated patency of the APD by observing the leakage of contrast medium from the MIP on fluoroscopy or radiography. 11,12,14 However, in many cases, the orifice of the MIP is very small and precise evaluation of patency of the APD is practically impossible using these methods.…”
Section: Patency Of the Apdmentioning
confidence: 99%
“…[46][47][48][49] Patency of the APD in control cases, as determined by dye-injection ERP, was 43% 49 , consistent with the average reported patency (46%; 624/ 1351). [2][3][4][5][6][7][8][9][10][11][12][13][14]37 In addition, Millbourn 4 reported that the APD was considered capable of relieving the function of the MPD in 33% of 182 cases.…”
Section: Dye-injection Erpmentioning
confidence: 99%
See 1 more Smart Citation
“…It is hypothesized that in some patients an increased resistance to flow across this small orifice results in dorsal duct hypertension and clinical symptoms [7,8]. The resulting increased dorsal duct pressure also may make the pancreas more prone to injury from alcohol and drugs [13,14]. This would explain why individuals with a relatively common anomaly rarely develop complications.…”
Section: Clinical Significancementioning
confidence: 99%